The clinical application of mesenchymal stromal cells in hematopoietic stem cell transplantation. Issue 1 (December 2016) - Zhao, Ke; Liu, Qifa
Abstract Mesenchymal stromal cells (MSCs) are multipotent stem cells well known for repairing tissue, supporting hematopoiesis, and modulating immune and inflammation response. These outstanding properties make MSCs as an attractive candidate for cellular therapy in immune-based disorders, especially hematopoietic stem cell transplantation (HSCT). In this review, we outline the progress of MSCs in preventing and treating engraftment failure (EF), graft-versus-host disease (GVHD) following HSCT and critically discuss unsolved issues in clinical applications.